2019
DOI: 10.31703/gssr.2019(iv-iii).12
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Effect on Secondary School Students Achievement in Mathematics

Abstract: This study provides the empirical support that how feedback support students to improve their achievement in mathematics. The sample of the study was 87 students of Mathematics in grades IX. There were 43 students in the control group and 44 students in the experiment group. Groups were matched on students’ results in Mathematics in grade 8 to ensure the equivalence of both groups. Furthermore, a pretest was also conducted to confirm equivalence. The researcher employed different techniques and strategies of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In our study, however, no significant difference was found between married and un-married regarding the use of collaborating, avoiding, and accommodating conflict management styles. Feedback and Students Engagement also have positive effect on students achievements and attitudes of both male and female students (Batool, & Akhter, 2019;Batool & Akhtar, 2020;Batool, Akhter, & Kalsoom, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, however, no significant difference was found between married and un-married regarding the use of collaborating, avoiding, and accommodating conflict management styles. Feedback and Students Engagement also have positive effect on students achievements and attitudes of both male and female students (Batool, & Akhter, 2019;Batool & Akhtar, 2020;Batool, Akhter, & Kalsoom, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to this perspective, students' use of a variety of cognitive and metacognitive techniques to control their thinking, acting, and inspiration during self-regulated learning may be suitable for developing an abstract understanding of mathematics and science as well as for gaining insight and understanding the concept. Students can also be engaged by giving them proper feedback, may be feedback can effect on low achiever more effectively but at every level it is source of better achievement (Batool, & Akhter, 2019). Therefore, the present study is designed to conduct on secondary school mathematics students to get insight into the engagement in this subject and the relationship with self-regulation and student achievement in mathematics.…”
Section: ____________________________________________________________...mentioning
confidence: 99%